2000
DOI: 10.1099/00207713-50-6-1973
|View full text |Cite
|
Sign up to set email alerts
|

Bartonella birtlesii sp. nov., isolated from small mammals (Apodemus spp.).

Abstract: Three strains isolated from Apodemus spp. were similar to Bartonella species on the basis of phenotypic characteristics. Futhermore, genotypic analysis based on sequence analysis of the 16S rRNA and gltA genes and on DNA-DNA hybridization showed that the three isolates represented a distinct and new species of Bartonella. The name Bartonella birtlesii is proposed for the new species. The type strain of B. birtlesii sp. nov. is IBS 325 T (l CIP 106294 T l CCUG 44360 T ).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
39
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(45 citation statements)
references
References 28 publications
5
39
0
Order By: Relevance
“…Color images available online at www.liebertpub.com/vbz vinsonii , B. doshiae, B. grahamii, and B. taylorii (Birtles et al 1995), B. tribocorum (Heller et al 1998), B. vinsonii subsp. arupensis (Welch et al 1999), B. birtlesii (Bermond et al 2000), B. washoensis , B. phoceensis and B. rattimassiliensis (Gundi et al 2004), B. rochalimae (Lin et al 2008), B. tamiae , B. rattaustraliani, B. queenslandensis, and B. coopersplainsensis (Gundi et al 2009), B. japonica and B. silvatica , and B. jaculi, B. callosciuri, B. pachyuromydis, and B. acomydis (Sato et al 2013). Other Bartonella isolated from rodents have been proposed as new species or subspecies, including Candidatus Bartonella washoensis subsp.…”
Section: Figmentioning
confidence: 99%
“…Color images available online at www.liebertpub.com/vbz vinsonii , B. doshiae, B. grahamii, and B. taylorii (Birtles et al 1995), B. tribocorum (Heller et al 1998), B. vinsonii subsp. arupensis (Welch et al 1999), B. birtlesii (Bermond et al 2000), B. washoensis , B. phoceensis and B. rattimassiliensis (Gundi et al 2004), B. rochalimae (Lin et al 2008), B. tamiae , B. rattaustraliani, B. queenslandensis, and B. coopersplainsensis (Gundi et al 2009), B. japonica and B. silvatica , and B. jaculi, B. callosciuri, B. pachyuromydis, and B. acomydis (Sato et al 2013). Other Bartonella isolated from rodents have been proposed as new species or subspecies, including Candidatus Bartonella washoensis subsp.…”
Section: Figmentioning
confidence: 99%
“…Bacterial DNA was extracted as previously described (4), and the 16S rRNA gene was amplified according to the previously published procedures (1,12). The amplified fragments were purified with a CHROMA SPIN 100 column (Clontech, Palo Alto, Calif.) according to the manufacturer's recommendations.…”
mentioning
confidence: 99%
“…During the last three decades, numerous surveys have been conducted in a variety of rodent communities at many locations. These surveys demonstrated that bartonellae are widely distributed in rodents of numerous species in all continents (Birtles et al,1994;Kosoy et al, 1997;Heller et al, 1998;Hofmeister et al, 1998;Laakkonen et al, 1998;Bermond et al, 2000;Fichet-Calvet et al, 2000;Bajer et al, 2001;Bown et al, 2002;Holmberg et al, 2003;Engbaek & Lawson, 2004;Gundi et al, 2004;Pawelczyk et al, 2004;Pretorius et al, 2004;Tea et al, 2004;Jardine et al, 2005;Kim et al, 2005;Telfer et al, 2005;Markov et al, 2006;Knap et al, 2007). The very first investigation of bartonella infection in rodents from tropic areas was conducted in Yunnan, a province located in southwestern China (Ying et al, 2002).…”
Section: Bartonella Infections In Rodents In Tropicsmentioning
confidence: 99%